Production of poly (3-Hydroxybutyrate-Co-3-Hydroxyvalerate) Using Comamonas sp. EB172 from Organic Acids Derived from Anaerobic Treatment of Palm Oil Mill Effluent - Mumtaz, Tabassum (2010)
Polyhydroxyalkanoates (PHAs) are biodegradable polymers accumulated by certain bacteria as intracellular carbon storage materials in response to inorganic nutrient limitation in the presence of excess carbon. Among the various types of PHAs, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), PHBV is the most promising and has great potential as a biodegradable substitute for bulk plastics. However, high production costs associated with substrates have limited the production of these polymers in large scale. In this study, the use of organic waste carbon compounds, in combination with anaerobic treatment, is being evaluated as alternative and appropriate substrates for PHBV production. Acidogenic fermentation of palm oil mill effluent (POME) generates a dilute mixture of organic acids (acetic acid, propionic acid and n-butyric acid) which, has to be recovered before being utilized by microbes for polymer biosynthesis. In this project, pilot scale recovery process was developed for obtaining a clarified solution of mixed organic acids to be used as substrates for PHBV production. The study also aimed at developing a novel fermentation strategy in 2 L scale and up-scaling the fermentation process in 150 L bioreactor based on constant impeller tip speed. The PHBV produced were further characterized and compared with the commercially available PHBV to address the market demand. Filtration and evaporation of treated POME for the recovery and clarification of organic acids was carried out using centrifugation and rotary evaporator in laboratory scale and filter press and rotary evaporator for pilot plant scale studies. When pilot scale set-up was used, the highest concentration obtained was 67.25 g/L upon eight-fold concentration with recovery yield of 83% as compared to 85% in laboratory scale. The effect of this clarified mixed organic acids on PHBV production by our local isolate, Comamonas sp. EB172 were evaluated in 2 L bioreactor. The time-course and utilization of carbon and nitrogen throughout the growth cycle of Comamonas sp. EB172 was compared using batch and fed-batch fermentation methods. Comamonas sp. EB172 showed higher tolerance of organic acids in the order of n-butyric acid>acetic acid>propionic acid. The fed-batch fermentation method was further simplified by eliminating the centrifugation step and operating the growth phase and PHA production phase consecutively in 2 L bioreactor. The fermentation was switched to PHA production phase by introducing nitrogen-free mineral media into the broth followed by mixed acids feeding using pH-stat method. By applying this strategy, the maximum biomass obtained in 2 L bioreactor was 10.2 g/L with residual acids around 2-6 g/L and volumetric productivity of 0.1318 g/L/ h. PHBV content ranged from 70- 90% (w/w) of the cell with yield of 0.27- 0.4 g PHBV/g mixed acid. Scaling up fermentation in 150 L bioreactor resulted in biomass concentration of 5.35 g/L with final PHBV content of 72.80% and volumetric productivity of 0.083 g/L/h. The calculated yield was 0.259 g PHBV/g mixed acids. Both yield and PHBV content were comparable to that obtained in 2 L scale. The final HV content in the copolymer ranged from 10-17%. In order to assess whether the poly (3-hydroxybutyrate-co-3-hydroxyvalerate) produced by Comamonas sp. EB172 could be used in practical applications, the physical, thermal and mechanical properties of the polymers were determined. The PHBV with 13% HV content exhibited the mechanical properties of elastic rubber and was less crystalline, having relatively low melting temperature and molecular weight of 130,000 Daltons. The chemical structure of the polymer was also confirmed by NMR and FTIR analyses. The size distribution of PHBV granules in Comamonas sp. EB172 ranged from 0.11 to 0.67 μm with 5-9 granules in each cell. TEM images of PHBV granules in vivo revealed core-shell structure indicating the formation of block copolymer instead of random copolymer. The overall results indicated that clarified organic acid mixtures derived from the partial anaerobic treatment of POME are suitable substrates for the production of PHBV. Therefore, the bioconversion of POME to PHBV via organic acids can be a useful way forward towards the sustainable utilization of POME wastewater.